Analysis of abutment safety factors against landslides on the Cipeundeuy bridge - Sukatani, Indonesia - Paikun; Amir Hamzah; Selfin Anugrah Amdania; Shcherbak Petr Nikolaevich (Nusa Putra University, 2021)
Bridges are connecting access between one region and another, and play an important role in transportation to facilitate community economic activities. The river bridge has very steep cliffs, and these cliffs often occur in landslides, therefore this study is very important to determine the safety of the bridge. This study aims to determine the safety of the bridge abutment structure which is the head of the bridge with the function of continuing the load on the bridge foundation. This analysis is limited to only calculating the stability and safety of bridge abutments with reinforced concrete structures. The analysis uses methods and formulas referring to Indonesian national standards, namely RSNI T-02-2005 regarding loading for bridges, RSNI T-12-2004 concerning concrete structure planning for bridges, SNI 03-2833-200X concerning earthquake resistance planning standards for bridges. The data used are drawing data and technical specifications used on the bridge, then the data is verified against planning consultants, project implementers, and observations at the location. The results of the analysis stated that the bridge abutment was declared safe from soil thrust and other forces, but did not have a good safety factor against shear forces. Landslides that occur can be resisted by the bridge abutments. This research is expected to be followed up by policymakers to repair bridges so that they are resistant to maximum shear forces, and provide safety signs from landslides to relieve public anxiety when crossing bridges, as well as provide reinforcement for the cliffs around the bridge.